Analytical validation of genotyping assays in the biomarker laboratory. (April 2007) - Isler, Jennifer A; Vesterqvist, Ole E; Burczynski, Michael E
High-throughput, whole-genome association studies conducted in various diseases and therapeutic settings are identifying an increasing number of single nucleotide polymorphisms that may predict patient responses and ultimately guide therapeutic decision-making. In order to confirm the candidate genetic markers emerging from these studies, there is a commensurate need for pharmacogenomic laboratories to design and analytically validate targeted genotyping assays capable of rapidly querying the identified individual single nucleotide polymorphisms of interest in large confirmatory clinical studies. In recent years, a number of increasingly complex technologies have been applied to the qualitative and semi-quantitative analysis of polymorphisms and mutations in DNA. The different approaches available for targeted DNA sequence analysis are characterized by various pros and cons that often present technology-specific challenges to the analytical validation of these assays prior to their use in clinical studies. Several key principles in the analytical validation of genotyping assays –– including assay specificity, sensitivity, reproducibility and accuracy –– are covered in this review article, with specific attention paid to three major end point detection technologies currently employed in targeted genotyping analysis: matrix-assisted laser desorption ionization time-of-flight mass spectrometry, Pyrosequencing ®® and Taqman ®® -based allelic discrimination. Thorough assessment of the performance of genotyping assays during analytical validation, and careful use of quality controls during sample analysis, will help strengthen the quality of pharmacogenomic data used to ultimately confirm the validity of exploratory biomarkers in DNA.